Women’s changing domestic responsibilities in neoliberal Africa: A relational time-space analysis of Lesotho’s garment industry - Ansell, Nicola; Tsoeu, Seroala; Hajdu, Flora (Gender, Place and Culture, 2015)
Since 2001 when Lesotho embraced the neoliberal African Growth and Opportunities Act that offers preferential access to the US market, its garment industry has expanded dramatically to become the nation’s leading employer. Elsewhere, large-scale employment of women in low-paid factory jobs has entailed spatial restructuring of gender and age relations. Lesotho is a distinctive context, with socio-spatial relations historically adjusted to male labour migration, high levels of contemporary male unemployment and alarming AIDS prevalence. Based on semi-structured interviews with 40 female factoryworkers and 37 dependents, this article applies a relational timespace analysis to explore how financial and spatio-temporal aspects of factory employment articulate to alter women’s relationships with those for whom they have culturally determined responsibilities: their children, those suffering from ill health and their (generally rural) home communities. The analysis highlights that such employment is not merely adding to women’s responsibilities, but transforming how they are able to undertake social reproduction, as practical, social and emotional roles are converted to largely financial obligations. © 2014 Taylor & Francis.
Keywords: 2000 à aujourd'hui; afrique; conciliation famille-travail; famille; lesotho; projet charge mentale; périodes historiques; ressource en ligne; régions géographiques; thématiques; travail

How microfinance empowers women in Côte d’Ivoire - Binaté Fofana, Namizata; Antonides, Gerrit; Niehof, Anke; van Ophem, Johan A. C. (Review of Economics of the Household, 2015)
This study deals with the effect of microcredit on women’s livelihood and empowerment in rural areas of Cote d’Ivoire. A cross-section survey was conducted among 185 borrowers from two microfinance institutions and 209 nonborrowers in rural areas of Cote d’Ivoire. In addition, a focus group discussion was held with each of the two women groups. After matching the two groups on the probability of obtaining credit, we found that the microcredit group on average had a higher income and a higher value of household assets than the non-borrowers. No differences in the value of personal women’s assets were found. Furthermore, on one hand women’s decision-making power in the household, as indicated by their strategic gender needs, was positively related to the probability of obtaining microcredit. On the other hand receiving microcredit tended to increase their decisionmaking power.
Keywords: OFDIG; afrique; autodétermination; côte d'ivoire; discipline; femmes*; microfinance; militance; ressource en ligne; régions géographiques; sciences de la gestion; thématiques; économie

Chroniques d'une musulmane indignée - Ibnouzahir, Asmaa (Fides, 2015)
En plus d'un récit autobiographique racontant les défis qu'elle a relevés en tant que jeune immigrante musulmane d'origine marocaine arrivée au Québec en 1994, Asmaa Ibnouzahir présente également une analyse éclairante sur des questions qui reviennent souvent dans nos médias au sujet de l'islam, des femmes et de la société: les musulmans «modérés», les crimes «d'honneur», le foulard, le féminisme islamique et bien d'autres. Islamiste pour certains et hérétique pour d'autres, Asmaa Ibnouzahir partage avec nous son parcours personnel et militant qui a fait d'elle la citoyenne québécoise musulmane, féministe et indignée qu'elle est aujourd'hui. Engagée dans les débats sociopolitiques qui ont traversé le Québec au cours de la dernière décennie, sur la religion, l'immigration et les valeurs québécoises, Asmaa Ibnouzahir livre un témoignage essentiel qui donne un accès sans précédent aux coulisses de ces débats. Depuis une dizaine d'années, Asmaa Ibnouzahir est engagée dans la réflexion et les débats sociaux autour des droits de la personne, notamment sur les questions touchant autant à l'immigration et à la religion dans la sphère publique qu'au statut des femmes dans l'Islam. Elle a également voyagé et travaillé dans plus d'une quinzaine de pays en tant que spécialiste de la nutrition d'urgence humanitaire. – [Renaud-Bray].
Section: 367 pages ; 23 cm
Keywords: 1900-1999; 1990-1999; 2000 à aujourd'hui; 2000-2009; 2010-2019; afrique; amériques; approches et analyses; canada; com5170; corps; cours; discipline; droits des femmes*; droits des personnes; féminisme islamique; immigration; maroc; point de vue situé; premier cycle; périodes historiques; québec; religion; régions géographiques; science politique; science politique et droit; thématiques

Gender and the political economy of land in Africa - Kouamé, Euphrasie B.H.; Fofona, Namizata B. (United Nations University Institute for Natural Resources in Africa, 2015)
Evidence shows that secure land rights have positive effects on poor people in general and women in particular, especially where households previously had little security. Several countries in Africa have been undertaking land reform initiatives that prohibit gender-based discrimination; however, the results revealed a substantial gap between the development of laws and their effective implementation. This paper draws attention to the political systems within which land tenure and property rights operate, especially for women. It also points out the main challenges in securing women’s land rights in Africa and highlights the economic, social and environmental benefits of increasing women’s access to land. The analysis shows that although many of the changes in policy and law appear to be legal and technical, access to and control over land is in practice related to socio-economic characteristics and governed by cultural practices and power relations at the family, community and country levels. The paper therefore recognizes the need for innovative approaches that go beyond property rights in operationalising strategies that strengthen women’s access to land. It is not enough for land legislation to be gender-sensitive; it must be gender-transformational. Land markets could potentially contribute to this transformation but their role is still limited by poor institutional capacity. The roles that different actors (women, men, women’s organizations, community leaders, donors) can play would be crucial in the process of securing women’s access to land in Africa.
ISBN: 9789988633066
Keywords: 2000 à aujourd'hui; 2010-2019; OFDIG; afrique; approches et analyses; femmes*; genre; identités LGBTQIA2+; politique; périodes historiques; rapports sociaux de sexe; ressource en ligne; régions géographiques; thématiques; égalité des sexes